PERSEPSI MAHASISWA AKUNTANSI TERHADAP KEGIATAN ASISTENSI MATA KULIAH - Wahyuningrum, Rany; Ludigdo, Unti (Jurnal Ilmiah Mahasiswa FEB, 2014)
The main purpose of this research is to understand studentâ€™s perception about course assistancy activities of Bachelor degree students Majoring in Accounting of Economics and Business Faculty, Brawijaya University. This assistancy activities measured by three indicators, i.e the implementation of assistancy activities, the competency of teaching assistant, and the benefit of assistancy activities. This research was held based on quantitative approachÂ  using frequency test, validity test, reliability test, and descriptive analysis. The results show that students gave positive perception about assistancy activities. 60% respondents of this research agreed and the other 25 % of respondents strongly agreed with this assistancy activities. It showed that assitancy activities in accounting student FEB-UB has already been performed properly. According to the questionnaire analysis result of three indicators, each result shows that 58% respondents agreed with assistancy activities that has been well implemented, 66% respondents says that teaching assistants have very good academic competences, and 55% respondents described that assistancy activities could give very much benefits to the student, respectively. Keywords : Perception, assistancy activities, students, teaching asisstant.